Literasi Keuangan Dan Inklusi Keuangan Syariah Di Kalangan Tenaga Pendidik Kabupaten Kuningan - Amir Hamzah (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2019)
This research aims to examine indicators that financial literation and sharia financial inclusion. The object of this research is the education staff in Kuningan Regency. The data collection technique used questionnare model with random sampling technique of 200 respondent. The research method is quantitative and the data analysis tool used Structural Equation Modeling (SEM) with Software Lisrel. The results of this study is financial attitude significant positive on Sharia financial inclusion, financial behavior significant positive on Sharia financial inclusion, and financial knowledge significant positive on Sharia financial inclusion.